A 2.5D coupled FEM–SBM methodology for soil–structure dynamic interaction problems. (1st January 2022) - Liravi, Hassan; Arcos, Robert; Clot, Arnau; Conto, Kenny F.; Romeu, Jordi
Abstract: In this paper, a novel numerical methodology to deal with longitudinally invariant soil–structure interaction problems is proposed. The methodology uses the finite element method to model the structure and the singular boundary method to model the wave propagation in the soil, both formulated in the wavenumber–frequency domain. The versatility presented by the finite element method combined with the simplicity and computational efficiency of the singular boundary method results in a friendly, robust and accurate novel methodology to address the soil–structure interaction problems. The accuracy of the proposed method is assessed by comparing it against 2.5D FEM–MFS and 2.5D FEM–BEM approaches for two cases: a thin cylindrical shell and a star-like beam structure, both embedded in a full-space medium. Moreover, the computational efficiency of the proposed method is evaluated against 2.5D FEM–MFS and 2.5D FEM–BEM methods. In the final step, the applicability of the proposed method is studied through an example of a railway tunnel embedded in a layered half-space. The results presented in this work exhibit the advantages of the novel approach in modelling simplicity, numerical efficiency and robustness with respect to previous methodologies. Highlights: A novel methodology for 2.5D soil–structure interaction problems is developed. As a novelty, a 2.5D SBM approach is used to model the soil. A 2.5D FEM approach is used to model the structure. This coupled 2.5D FEM–SBM is simpler and more efficient than previous approaches. Its application for railway-induced vibration assessment is presented.